Estructura espacial y temporal de la ictiofauna del Estero de Tamarindo, Parque Nacional Marino Las Baulas, Costa Rica - Ortiz-Araya, Scarleth (2018)
Abstract: Spatial and temporal structure of the ichthyofauna of the Estuary of Tamarindo, Las Baulas National Marine Park, Costa Rica. Fish communities in mangrove areas have an ecological and socio-economic importance. The management in this kind of habitat is based on the data information about spatial and temporal patterns. The main goal of the study is determinate the spatial and temporal structure of the ichthic community from Tamarindo mangrove area. Six samplings trips were conducted from August 2009 to June 2010, at five mangrove stations using four different fishing gear. Also, environmental variates were recording (temperature, oxygen, salinity, pH, and water transparency). A total of 1357 individuals belonging to 59 species of 28 families were identified. Carangidae and Lutjanidae were more richness families, and the most abundant were Poecilidae, Mugilidae and Clupeidae. Poeciliopsis elongata was the most abundant species. Temporally, the diversity reached a minimum of 1.55 in December and a maximum of 1.96 in April. The richness presented a minimum of 22 species in February and a maximum of 25 in December. Spatially, the diversity reached a minimum of 1.96 in the mouth of the estuary and a maximum of 2.79 in mid estuary; the richness a minimum of 24 species inner the estuary and a maximum of 30 at mid estuary. Additionally, a temporal pattern of succession of species was determined. The fish community shows change in the similarity in their species composition from the mouth to the inner part of the estuary. At inner of the estuary the abundance was low, in contrast with the richness, diversity and equitability. Finally, nursery process for some key species for fisheries occurs in this estuary; made it fragile and susceptible to pollution and anthropogenic impacts, because their short mangrove area and shallow depth. Rev. Biol. Trop. 66(Suppl. 1): S255-S268. Epub 2018 April 01.